Pengaruh Konsumsi Berita Online terhadap Tingkat Kepercayaan Mahasiswa pada Media Massa (Studi pada Kompas.com) - Agustin, Yoselia Fira; Putra, Delfan Eko (Lembaga Yasin AlSys, 2026)
The development of digital media has changed students’ patterns of obtaining information, particularly through online news portals such as Kompas.com. This study aims to analyze the effect of online news consumption on the level of students’ trust in mass media. This study used a quantitative approach with an explanatory survey design. The research respondents consisted of 20 students selected through purposive sampling based on the criterion of having accessed or read news through Kompas.com. Data were collected using a closed-ended Likert-scale questionnaire consisting of 16 statement items, namely eight items for the online news consumption variable and eight items for the student trust level variable. Data were analyzed using descriptive statistics, validity testing, reliability testing, and simple linear regression. The results show that online news consumption has a positive and significant effect on the level of students’ trust in mass media, with a regression coefficient of 0.797 and a significance value of 0.000 < 0.05. The coefficient of determination value of 0.954 indicates that online news consumption explains 95.4% of the variation in students’ level of trust. This finding confirms that online news consumption plays an important role in shaping students’ trust in mass media. The implications of this study provide a basis for digital media managers to improve the quality of news presentation that is credible, informative, and relevant to student readers.